Enviroshopping for Teens - Linda B. Bobroff; R. Elaine Turner (EDIS, 2012)
Every day, we make choices that impact our environment. This revised 3-page fact sheet will help you make environmentally friendly choices whenever you make purchases and encourage you to take a second look at items before throwing them away. Written by Linda B. Bobroff and R. Elaine Turner, and published by the UF Department of Family, Youth and Community Sciences, September 2012.